PIROLISIS BIOMASSA: REVIEW - Nur Aini Aini; Siti Jamilatun; Joko Pitoyo (Agroindustrial Technology Journal, 2022)
The exploitation of fossil energy causes non-renewable reserves to dwindle and causes global warming; climate change endangers living things. Energy sources from the second generation, namely lignocellulosic-based biomass, provide development opportunities, not interfere with food reserves, and are easy to cultivate. One technology that is feasible to use to treat lignocellulosic biomass is pyrolysis. Pyrolysis can convert lignocellulosic biomass (including cellulose, hemicellulose, and lignin) into solid, liquid, and gaseous. The pyrolysis mechanism by thermal decomposition goes through several stages, namely charcoal formation, depolymerization, fragmentation, and other secondary reactions. This paper provides insight into the pyrolysis of lignocellulose and its by-products. Several parameters, such as reaction environment, temperature, residence time, and heating rate, significantly affect the pyrolysis process.